INFORMATION AND PSYCHOLOGICAL SECURITY OF A PERSON IN THE HYBRID WARFARE CONDITIONS - Алещенко, В. (Київський національний університет імені Тараса Шевченка, 2022)
The article reveals the actualization of the problem of information and psychological security of the individual in a hybrid war. The normative and legal bases of information security as an important component of state security are given. The concepts of security, national security, information security, information-psychological, psychological security are analyzed. The basic criteria of psychological security of the person taking into account information influence are opened. External and internal factors of psychological mechanisms of informational influence on the individual, society, the state as a whole are considered. The main subjects and objects of information and psychological influence are identified. The issue of transformation of psychological security of the individual as a consequence of long-term information and psychological influence is actualized. The structural and functional model of information and psychological security of the individual is given. Theoretical and applied aspects of work with servicemen in the conditions of destructive information influences are summarized and considered. The directions of information and psychological attacks against Ukraine are singled out and the classification of information and psychological threats is given. The negative consequences of information-psychological influence on the psyche are determined and effective ways of counteracting the negative influence of information flows are given. It is emphasized that the control of the information environment, teaching the population the basics of media literacy, taking measures to protect the information environment from external negative influences, etc. contribute to improving the information and psychological security of the individual.

Досліджено актуалізацію проблеми інформаційно-психологічної безпеки особистості в умовах гібридної війни. Наведено нормативно-правові основи інформаційної безпеки як важливої складової безпеки держави. Проаналізовано поняття безпека, національна безпека, інформаційна безпека, інформаційно-психологічна, психологічна безпека. Розкрито основні критерії психологічної безпеки особистості з урахуванням інформаційного впливу. Розглянуто зовнішні та внутрішні фактори психологічних механізмів інформаційного впливу на особистість, суспільство, державу в цілому. Визначено основні суб'єкти та об'єкти інформаційно-психологічного впливу. Актуалізовано питання трансформації психологічної безпеки особистості як наслідку тривалого інформаційно-психологічного впливу. Наведено структурно-функціональну модель інформаційно-психологічної безпеки особистості. Узагальнено та розглянуто теоретико-прикладні аспекти роботи з військовослужбовцями в умовах деструктивних інформаційних впливів, що вимагають обов'язкового врахування органами військового управління ЗСУ, для забезпечення ефективності роботи з військовослужбовцями під час вирішення завдань за призначенням. Виокремлено напрями інформаційнопсихологічних атак проти України та наведено класифікацію інформаційно-психологічних загроз. Визначено негативні наслідки інформаційно-психологічного впливу на психіку та наведено ефективні способи протистояння негативному впливу інформаційних потоків. Підкреслено, що підвищенню інформаційно-психологічної безпеки особистості сприяють контроль інформаційного середовища, навчання населення основам медіаграмотності, проведення заходів щодо захисту інформаційного середовища від зовнішніх негативних впливів тощо.
ІНФОРМАЦІЙНО-ПСИХОЛОГІЧНА БЕЗПЕКА ОСОБИСТОСТІ В УМОВАХ ГІБРИДНОЇ ВІЙНИ
Keywords: information space; information-psychological security; information-psychological influence; moral-psychological state; informationpsychological stress; інформаційний простір; інформаційно-психологічна безпека; інформаційно-психологічний вплив; морально-психологічний стан; інформаційно- психологічний стрес